Upaya Menumbuhkan Karakter Peduli Lingkungan Melalui Kajian Konsep Fisika Pada Arsitektur Kearifan Lokal Budaya Sumatera Barat - Afrizon, Renol; Dwiridal, Letmi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
The utilization of local wisdom in presentation of physics material of high school grade XI  by physics education students is still not optimal. This indicates that the students who careless by sense of environmental. Physics learning resources in daily activities such as local wisdom needed to provide. The purpose of this study is to explore the application of physics concepts to local wisdom of West Sumatra culture as an effort to improve the character of environmental care. The type of research is qualitative research with survey method. Data collected by questionnaires, interviews, document analysis, field notes and Focus Group Discussion (FGD). Analyzed techniques of data which be used qualitative data techniques with steps are data reduction, presentation, conclusion and verification as data analyzed techniques. Result of the research is physics concepts of Rumah Gadang. First, although the Rumah Gadang roof was made of palm fiber but it still survive from leakage problems and wind exposure. The functions of the roofing of the Rumah Gadang are: (1) to increase the speed of the rain falling into the roof, (2) minimize the momentum on the roof, (3) projecting the force of the wind in all directions so that the wind is not trapped on the roof of the Rumah Gadang, 4) made of adhesive between kitchen ash with a good palm fiber (deep layer of palm fiber ), and 5) water deposition on the bad side of palm fiber (outer layer of palm fiber) so that it will be rise to back the surface of the roof through the capillarity mechanism. Second, the wall with a hollow layer can reduce the heat from outside the walls during the day so the air in the room is not as hot as the outside and the heat that has flowing in the room will be trapped by the wall so that air is not too cold at the night. Third, old pole serves as a reference to determine the equalibrium of Rumah Gadang and the poles are made with a slope which opposite direction on two sides (left and right house). This can be create a stable of equalibrium Rumah Gadang. Fourth, a stone of fondation that has a diameter greater than the diameter of the milestone can serve to minimize the fictive forces generated by the soil due to the occurrence of the earthquake. Fifth, the staircase made with a certain slope provides a distinct mechanical advantage for the visitor where the where the produced work made becomes as easier. The conclusions of this research indicates this study provide one of the efforts to improve the character of environmental care in physics learning.